COOPERATION BETWEEN TEACHERS AND STUDENTS AS BASIS OF PERSONALITY-ORIENTED TEACHING (Pedagogy of Higher and Secondary Education, 2001)
The article examines the problem of cooperation of a teacher and pupils as a basis of personally oriented teaching. The reasons of a low-level of pupils' cognitive, creative activity in the educational process are studied. Special attention is paid to dialogic teaching, which lies in the basis of cooperation of a teacher and pupils, and to the requirements of the organization of educational dialogue.